Conceptual design of a combined brake-accelerator pedal for limbs disabled driver using a hybrid approach - Suliano, Salami Bahariah; Ahmad, Siti Azfanizam; As’arry, Azizan; Abdul Aziz, Faieza (Universiti Putra Malaysia Press, 2023)
This paper presents the conceptual design of a combined brake-accelerator pedal for limbs disabled drivers using a hybrid approach. A hybrid in which it consists of a combination of TRIZ for design generation, a Morphological Chart for design composition, and a Pugh Matrix for design selection. The aim is to generate and select the best concept design for a combined brake-accelerator pedal with special attention based on the needs of the disabled’s ergonomics. In this paper, the function analysis, cause, and effects analysis, TRIZ contradiction matrix, and 40 Inventive principles were applied in the solution generation stage. The outcomes of solutions proposed in TRIZ were then refined using a Morphological chart to deliberate the design composition of the combined brake-accelerator pedal. As a result, three innovative design concepts of combined brake-accelerator pedals were produced. Pugh Matrix was finally utilized to perform multi-criteria scoring based on the baseline to select the best ergonomics concept for combined brake-accelerator pedals for disabled drivers.